The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1186/s40561-021-00156-9
|View full text |Cite
|
Sign up to set email alerts
|

Instructional improv to analyze inquiry-based science teaching: Zed’s dead and the missing flower

Abstract: In inquiry-based science lessons teachers face the challenge of adhering to curricular goals while simultaneously following students’ intuitive understandings. Improvisation (improv) provides a useful frame for understanding teaching in these inquiry-based contexts. This paper builds from prior work that uses improv as a metaphor for teaching to present a translated model for analysis of teaching in an inquiry-based, elementary school science lesson context. We call our model instructional improv, which shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…to pose questions to guide the student inquiry process. Research shows that in an inquiry learning environment, questions can serve to challenge students’ inconsistent views; help them to articulate their initial concepts; elicit their ideas to resolve confusion, and assist them to explain, elaborate and reflect on their understanding (Chin, 2007; Dahn et al , 2021; Syahmani et al , 2021). Therefore, as a surrogate for teacher questioning in an online module, the POEE method uses five types of inquiry questions: cognitive conflict, question prompts, concept check, confidence check and multiple-choice questions.…”
Section: Methodsmentioning
confidence: 99%
“…to pose questions to guide the student inquiry process. Research shows that in an inquiry learning environment, questions can serve to challenge students’ inconsistent views; help them to articulate their initial concepts; elicit their ideas to resolve confusion, and assist them to explain, elaborate and reflect on their understanding (Chin, 2007; Dahn et al , 2021; Syahmani et al , 2021). Therefore, as a surrogate for teacher questioning in an online module, the POEE method uses five types of inquiry questions: cognitive conflict, question prompts, concept check, confidence check and multiple-choice questions.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments have shown that IBS teaching improves students' cognitive and affective characteristics, as well as their critical thinking abilities (Koksal & Berberoglu, 2014;Ku et al, 2014). Recently, IBS teaching with Prediction-Observation-Explanation (Zhao et al, 2021), improvisation (Dahn et al, 2021), virtual reality (Lai et al, 2022), and digital practice (de Jong et al, 2021;Song & Wen, 2018), some methods and techniques seem to be combined. In addition, the relationships between IBS and variables such as learning, attitude, achievement, and interest are still being investigated (Salchegger et al, 2021;Chi et al, 2021;Stender et al, 2018;Kang & Keinonen, 2018).…”
Section: What Is Ibs?mentioning
confidence: 99%
“…Inquiry-based teaching with these elements is one of the most described goals for quality science education and scientific literacy instruction (Bybee & McCrae, 2011;Abd-El-Khalick & Lederman, 2000). Inquiry-based science (IBS) education is still useful for 21st-century education reform and professional science education (Song & Wen, 2018;Chu et al, 2021;Dahn et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to use a variety of strategies to get pupils to use their existing knowledge (Brod et al, 2018). Teachers must adjust their lesson plans, activities, and imagined conversations to match the behaviors that take place in the classroom with the knowledge that students are ready to acquire (Dahn et al, 2021).…”
Section: A Introductionmentioning
confidence: 99%